Mevlana’nın Nazarında Ölüm / Death in Mowlawee’s View - Uğurlu, Tuğberk (Journal of History Culture and Art Research, 2016)
Death in Mowlawee’s View Death is one of the main obsessions of man and ranks among his most sophisticated mental and spiritual enigmas. It is hard to accept that there will come a day when we will have to abandon all our mundane attachments to set out a journey to an unknown world. Islamic mystics and sophis even went farther. They regarded death not only as a beginning of a new life but also as a means to reunite with the Eternal Beloved from whom they had been detached by their mundane life. Therefore they consider death as an auspicious event which they always welcome cheerfully and the arrival of which they long for. In this essay, writer constitutes the main topic of the conversation as Mawlana’s opinion about death who is one of most famous intellectual and mystic of Islam history. By doing this, he uses Mawlana’s most notorious compositions ‘Masnawi’ and ‘Fihi Ma Fih’. In the essay, from the opinion of Mawlana as ’death is not an annihilation but a door which anybody has to pass for a new and brighter start’ influenced strongly. Mevlana’nın Nazarında Ölüm Ölüm, insanın başlıca endişelerinden biridir ve onun karmaşık akli ve manevi muammalarının içerisinde üst sıralardadır. Günün birinde, tüm dünyevi bağlarımızı ardımızda bırakıp bilinmeyen bir dünyaya yolculuğa çıkacağımızı kabul etmek zordur. İslam mistisistleri (Sufiler) bu konuda daha da ileri gitmişlerdir. Onlara göre ölüm sadece yeni bir hayata başlangıç değil, aynı zamanda dünya hayatında gurbet çektikleri “Ebedi Sevgili”ye kavuşmak manası taşır. Bu yüzden ölümü her zaman neşeyle karşılanacak, hasret çektikleri şeye kavuştukları kutlu bir olay olarak görürler. Bu makalede yazar, İslam tarihinin belki de en meşhur sufi ve düşünürü Hz. Mevlana’nın ölüm konusundaki yaklaşımlarını konu edinmiştir. Bunu yaparken de ekseriyetle onun en meşhur eserleri; ’Mesnevi’ ve ’Fihi Ma Fih’den faydalanmıştır. Makalede Hz. Mevlana’nın ölümü bir yok oluş değil, yeni ve daha parlak bir başlangıca açılan geçilmesi zaruri bir kapı olarak gördüğü düşüncesi ağırlıktadır.